2020
DOI: 10.1007/s40820-020-0404-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Persistent Luminescence Nanoparticles in Bioapplications

Abstract: Persistent luminescence phosphors are a novel group of promising luminescent materials with afterglow properties after the stoppage of excitation. In the past decade, persistent luminescence nanoparticles (PLNPs) with intriguing optical properties have attracted a wide range of attention in various areas. Especially in recent years, the development and applications in biomedical fields have been widely explored. Owing to the efficient elimination of the autofluorescence interferences from biotissues and the ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 171 publications
1
92
0
Order By: Relevance
“…Persistent luminescent nanoparticles (PLNPs) can be synthesised by various methods including both sol–gel and template chemistry, with MSNs, as of writing this review, the only successful template offering control over morphology [ 136 ]. MSN templates can, for example, be used to generate multifunctional MSN/PLNP nanocomposites with Li et al reporting a facile fabrication of persistent luminescent SrMgSiO 6 :Eu 2+ 0.01 ,Dy 3+ 0.02 nanocomposites by a high-temperature conversion of the metal (Sr 2+ , Mg 2+ , Eu 2+ , Dy 3+ ) impregnated MCM-41 [ 137 ].…”
Section: Optical Imagingmentioning
confidence: 99%
“…Persistent luminescent nanoparticles (PLNPs) can be synthesised by various methods including both sol–gel and template chemistry, with MSNs, as of writing this review, the only successful template offering control over morphology [ 136 ]. MSN templates can, for example, be used to generate multifunctional MSN/PLNP nanocomposites with Li et al reporting a facile fabrication of persistent luminescent SrMgSiO 6 :Eu 2+ 0.01 ,Dy 3+ 0.02 nanocomposites by a high-temperature conversion of the metal (Sr 2+ , Mg 2+ , Eu 2+ , Dy 3+ ) impregnated MCM-41 [ 137 ].…”
Section: Optical Imagingmentioning
confidence: 99%
“…Inspired by these characteristic advantages of PLNPs, an increasing number of researches have been reported for PLNPsbased bioimaging and therapy. Though some reviews have been shown from different aspects of PLNPs field [7,9,[17][18][19][20][21], it is still important to make a new summarization to stress on the cancer theranostics application using the rational designed PLNPs nanoplatforms.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, PLMs can keep emitting light without continuous in situ excitation by which the autofluorescence interference elicited by biological system itself can be effectively eliminated and accordingly provide superior signal‐ to‐noise ratio (SNR). [ 8 ] Hence, PLMs’ remarkable performance makes long‐term bioimaging possible and greatly improves the sensitivity of biosensing and bioimaging comparing with conventional luminescence materials. Considered to be a class of excellent optical probes, PLMs have therefore gained extensive attention and opened up new directions in biomedicine and bioanalysis fields.…”
Section: Introductionmentioning
confidence: 99%
“…summarized the advances of PLMs in synthesis methods, bioapplications, biosafety and biomembrane modification. [ 8 ] Yuan et al . recently highlighted the progress in designing near‐infrared (NIR) PLMs‐based probes and their applications in time‐resolved bioimaging and biosensing.…”
Section: Introductionmentioning
confidence: 99%